Recently Investigated Natural Gums and Mucilages as Pharmaceutical Excipients: An Overview. (7th April 2014) - Choudhary, Pritam Dinesh; Pawar, Harshal Ashok
Abstract : Due to advances in drug delivery technology, currently, excipients are included in novel dosage forms to fulfil specific functions and in some cases they directly or indirectly influence the extent and/or rate of drug release and drug absorption. Recent trends towards use of plant based and natural products demand the replacement of synthetic additives with natural ones. Today, the whole world is increasingly interested in natural drugs and excipients. These natural materials have many advantages over synthetic ones as they are chemically inert, nontoxic, less expensive, biodegradable, and widely available. This review discusses majority of the plant-derived polymeric compounds (gums and mucilage's), their sources, chemical constituents, uses, and some recent investigations as excipients in novel drug delivery systems.